(untitled) (Comprehensive Journal of Science, 2025)
E-health system represents innovative technology that is reshaping modern healthcare delivery globally. However, low implementation exists among developing countries and the few adoption cases are characterized by massive implementation failure. The failure is mainly attributed to direct adoption of E-health models from other regions without considering the differences in context. Therefore, this study investigates the Moderating Effect of Political Readiness on between UTAUT factors (performance expectancy, effort expectancy, facilitating conditions) and TRI factors (optimism, innovativeness, discomfort, and insecurity) and E-health readiness in Libya. Through a survey questionnaire, data were collected from 369 Libya hospitals, and the hypotheses in the proposed model were tested by Partial Least Squares Structural Equation Modeling (PLS-SEM). The empirical results conﬁrm that the positive and significant effects of optimism, innovativeness, performance expectancy, effort expectancy, and political readiness on E-health readiness, while insecurity and discomfort were negative and significant. Furthermore, the results showed that political readiness positively and significantly affected the relationship among insecurity, optimism and EHR. However, political readiness proved to have a negative influence on the relationship between innovativeness, discomfort, facilitating conditions and EHR. These findings suggest important factors influencing EHR in Libya. Finally, this study contributes significantly to the successful transformation of the e-health system by raising the level of e-health readiness among users in Libya linked to the adoption of direct models from different socio-economic contexts. Other theoretical and practical implications derived from the findings, and the limitations and future research directions are also offered.